2018
DOI: 10.1111/ilr.12119
|View full text |Cite
|
Sign up to set email alerts
|

When two worlds collude: Working from home and family functioning in Australia

Abstract: This article analyses the effect of employees working from home on their partners' assessments of family functioning using Australian household panel data collected from 2001 to 2013 in 48 multivariate models. Some evidence is found that working from home contributes to better relationships and a more equitable division of household responsibilities for couples with children. Limited evidence of negative externalities is observed, notably where male employees work substantial hours from home. Overall the findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
58
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 28 publications
4
58
1
5
Order By: Relevance
“…And the third is the opportunity for leaders to achieve work-life balance is huge if they are able to practice eleadership and able to overcome all the challenges they face. In addition, by working from home, they also avoid the distractions they usually get in the office such as noise, crowds and other disturbances, by working from home they feel more comfortable and have more flexible work areas so that supervision and organizational control can be done simultaneously with responsibility for his family's duties, this supports the (Dockery & Bawa, 2018) findings and also (Cantera, Cubells, Martínez, & Blanch, 2009).…”
supporting
confidence: 66%
“…And the third is the opportunity for leaders to achieve work-life balance is huge if they are able to practice eleadership and able to overcome all the challenges they face. In addition, by working from home, they also avoid the distractions they usually get in the office such as noise, crowds and other disturbances, by working from home they feel more comfortable and have more flexible work areas so that supervision and organizational control can be done simultaneously with responsibility for his family's duties, this supports the (Dockery & Bawa, 2018) findings and also (Cantera, Cubells, Martínez, & Blanch, 2009).…”
supporting
confidence: 66%
“…Such barriers are also prevalent in precarious and unskilled areas of the economy have restricted access to flexible work practices ( van den Broek and Keating, 2009 ). There are other inequities in working from home, such as differences in outcomes to employed women and men with children, particularly in the areas of job satisfaction and satisfaction with the distribution of childcare tasks ( Troup and Rose, 2012 ), whereas other have found some evidence is found that working from home contributes to better relationships and a more equitable division of household responsibilities for couples with children ( Dockery and Bawa, 2018 ). With regards to COVID-19 it has been found that the impact has been disproportionately large on women ( Nash and Churchill, 2020 ; Craig and Churchill, 2020 , Lister 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sehingga terjadi penyesuaian-penyesuaian supaya jenis-jenis pekerjaan bisa dikerjakan secara jarak jauh (remote) tanpa mendatangi kantor ataupun perusahaan. Hal ini sesuai dengan penelitian dari Mustajab, et al (2020); Dockery & Bawa (2018); Lippe (2019) yang menyatakan banyaknya perusahaan telah menginstrusikan adanya kebijakan bekerja dari rumah untuk memutus rantai penyebaran Berdasarkan uraian di atas Work from everywhere yang pernah dilakukan di Indonesia secara masal hampir di semua sektor adalah sebelum dan saat terjadi pandemi covid-19, namun belum diketahui apakah Work from everywhere masih mungkin dilakukan setelah masa pandemi berakhir (era normal baru setelah covid-19)? Apakah mungkin cara kerja Work from everywhere ini akan menjadi sebuah normal baru dalam bekerja pada jenis-jenis pekerjaan yang umumnya tidak bisa dilakukan secara jarak jauh?.…”
Section: Pendahuluanunclassified